Compiuter technologies assist potential energy with experiments - Alizoti, Alion; Vila , Floran; Mulaj , Zenun; Dhoqina , Polikron (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Energy is an important physical quantity to study and reconstruct nature at our own leisure. Implementations of new tendencies in Physics show that energy, and other physical quantities, need careful examinations before being applied. Following international and national recommendations, our present work focused on several research studies concerning potential energy. A simple experiment was developed to verify the conservation of energy. At the end, the participants were convinced that it is really difficult to achieve the conservation of energy to its perfect form. They also ended with some intriguing conclusions, similar to the research studies this activity referred to.